2017
DOI: 10.3390/su9112135
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter (PM10 and PM2.5) in Subway Systems: Health-Based Economic Assessment

Abstract: Particulate matter (PM) is implicated in severely negative health effects, and subway-system PM is potentially more genotoxic than several other particle types. However, there are insufficient studies on subway-system PM-pollution reduction and control and the potential economic benefits thereof. Thus, the present study undertakes to assess the potential economic benefits resulting from a 10 µg/m 3 reduction in PM 10 and PM 2.5 concentrations in a subway system, and to evaluate the importance of prevention and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…These sources emit substances such as sulphur dioxide (SO 2 ), nitrogen dioxide and nitrogen oxides (NO x ), carbon oxides (CO x ) and particulate matter. Among the particulates, the most dangerous to health and life are fine particles with a diameter below 10 µm, which include PM2.5 and PM10 particulates [29]. Exposure to particulate matter (PM2.5) has been associated with increased cardiovascular outcomes [30].…”
Section: Introductionmentioning
confidence: 99%
“…These sources emit substances such as sulphur dioxide (SO 2 ), nitrogen dioxide and nitrogen oxides (NO x ), carbon oxides (CO x ) and particulate matter. Among the particulates, the most dangerous to health and life are fine particles with a diameter below 10 µm, which include PM2.5 and PM10 particulates [29]. Exposure to particulate matter (PM2.5) has been associated with increased cardiovascular outcomes [30].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is reported that as the particle size decreases, the ability to penetrate into the lower airways will increase. 44 Nguyen et al 45 also reported that subway PM inhalation affects the heart and lungs and can cause serious health problems. These particles have been reported to increase the risk of respiratory-related diseases, such as irregular heartbeat, vascular disorders, lung cancer, arrhythmias, chronic obstructive pulmonary disease, asthma exacerbation, and cardiovascular-related diseases.…”
Section: Baffle Dust Collectormentioning
confidence: 99%
“…These compounds include sulphur dioxide (SO 2 ), nitrogen oxides (NO x ), carbon oxides (CO x ) and harmful particulates. Particulates with a diameter below 10 µm, including PM 2.5 and PM 10 , are considered to be the most harmful [51]. Direct inhalation of particulates (PM 2.5 ) is associated with an increased incidence of cardiovascular disease [52].…”
Section: Introductionmentioning
confidence: 99%